ANALISIS KESALAHAN BERBAHASA BIDANG SEMANTIK DALAM PIDATO MENTERI PENDIDIKAN DAN KEBUDAYAAN (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
In this study, researchers are interested in analyzing language errors in the field of semantics. The subject of this research is the speech of Nadiem Makarim (Minister of Education and Culture). The first speech is about National Teacher's Day 2020, and the second speech is about the commemoration of National Education Day 2021. The method used in this analysis is a qualitative method. The qualitative method shows that the analysis is only based on the facts contained in the speech of the Minister of Education and Culture (Nadiem Makarim). The technique used in this study to collect data is the technique of observing linguistic elements in the speech of the Minister of Education and Culture (Nadiem Makarim) and the technique of systematically recording language errors contained in the speech. In the Mendikbud's speech on the commemoration of National Teacher's Day 2020, there were seven semantic errors, namely in the words chain, laboratory, jump, stakeholder, walking, painter, and the word high. Meanwhile, from Nadiem Makarim's speech, in commemoration of National Education Day 2021, there are also seven semantic errors, namely in sheet words, grasping, breakthroughs, walking in place, leaps, fields, and stretched words. The technique used in this study is a technique for observing linguistic elements in the speech of the Minister of Education and Culture (Nadiem Makarim), and a technique for systematically recording language errors in speeches.